Bisphenol S exposure interrupted human embryonic stem cell derived cardiomyocytes differentiation through ER-NF-κB/ERK signaling pathway - Yongru Zhou; Lin Tian; Liang Wang; Wenjing Wu; Baofang Liang; Wei Xiong; Lishi Zhang; Xiaomeng Li; Jinyao Chen (Ecotoxicology and Environmental Safety)
Bisphenol S (BPS) has been put into production as a wide range of Bisphenol A (BPA) alternatives, while little is known regarding its cardiac developmental toxicity. To explore the effect of BPS on cardiomyocyte differentiation and its mechanism, our study established the human embryonic stem cell-cardiomyocyte differentiation model (hESC-CM), which was divided into early period of differentiation (DP1:1–8d), anaphase period of differentiation (DP2:9–16d) and whole stage of differentiation (DP3:1–16d) exposed to human-related levels of BPS. We found that the survival rate of cardiomyocytes was more sensitive to BPS at the early stage of differentiation than at the anaphase stage of differentiation, and exposure to higher than 30 µg/mL BPS throughout the differentiation period decreased the expression of cTnT. BPS may affect cardiomyocyte differentiation by activating ERβ-NF-κB/ERK signaling pathway, and the signaling pathway of each stage might be different. During DP1, 3 µg/mL of BPS may increase the inflammatory effect of cardiomyocytes mainly through the ERβ-NF-κB signaling pathway, thereby inhibiting cell proliferation, and leading to impaired cardiac function in early differentiation. During DP2, BPS may activate the ERβ-ERK signaling pathway, increase cardiomyocyte apoptosis, alter the establishment of the outer matrix, and thus affect myocardial differentiation. However, exposure to BPS throughout the differentiation stage may disrupt the immune response and cell differentiation, which in turn interrupts heart function. The benchmark dose lower confidence limit (BMDL) of the relative expression of cTnT mRNA exposed by BPS during DP3 was the lowest among all the BMDLs of a good fit, with BMDL5 of 1.96 × 10−2 µg/mL, which is lower than the current reported exposure levels of BPS in maternal serum (0.03–0.07 ng/mL) and maternal umbilical cord serum (0.03–0.12 ng/mL).